Effects of two alveolar recruitment maneuvers in an “open-lung” approach during laparoscopy in dogs - Di Bella, Caterina; Vicenti, Caterina; Araos, Joaquin; Lacitignola, Luca; Fracassi, Laura; Stabile, Marzia; Grasso, Salvatore; Crovace, Alberto; Staffieri, Francesco (Frontiers in Veterinary Science, 2022)
Objectives: To compare the effects of a sustained inflation alveolar recruiting maneuver (ARM) followed by 5 cmH2O of PEEP and a stepwise ARM, in dogs undergoing laparoscopic surgery. Material and methods: Twenty adult dogs were enrolled in this prospective randomized clinical study. Dogs were premedicated with methadone intramuscularly (IM); anaesthesia was induced with propofol intravenously (IV) and maintained with inhaled isoflurane in pure oxygen. Baseline ventilatory setting (BVS) was: tidal volume of 15 mL/kg, inspiratory pause of 25%, inspiratory to expiratory ratio of 1:2 and the respiratory rate to maintain the end-tidal carbon dioxide between 45 and 55 mmHg. Ten minutes after pneumoperitoneum, randomly, 10 dogs underwent sustained inflation ARM followed by 5 cmH2O of PEEP (ARMi), while 10 dogs underwent a stepwise recruitment maneuver followed by the setting of the “best PEEP” (ARMc). Gas exchange, respiratory system mechanics and hemodynamic were evaluated before the pneumoperitoneum induction (BASE), ten minutes after the pneumoperitoneum (PP), ten minutes after the recruitment (ARM) and ten minutes after the pneumoperitoneum resolution (PostPP). Statistical analysis was performed with ANOVA test (p < 0.05). Results: Static compliance decreased in both groups at PP (ARMc = 1.35 ± 0.21; ARMi = 1.16 ± 0.26 mL/cmH2O/kg) compared to BASE (ARMc = 1.78 ± 0.60; ARMi = 1.66 ± 0.66 mL/cmH2O/kg) and at ARM (ARMc = 1.71 ± 0.41; ARMi = 1.44 ± 0.84 mL/cmH2O/kg) and PostPP (ARMc = 1.75 ± 0.45; ARMi = 1.89 ± 0.59 mL/cmH2O/kg) it was higher compared to PP and similar to BASE. The PaO2/FiO2, in both groups was higher at ARM (ARMc = 455.11 ± 85.90; ARMi = 505.40 ± 31.70) and PostPP (ARMc = 521.30 ± 66.20; ARMi = 450.90 ± 70.60) compared to PP (ARMc = 369.53 ± 49.31; ARMi = 394.32 ± 37.72). Conclusions and clinical relevance: the two ARMs improve lung function in dogs undergoing laparoscopic surgery similarly. Application of PEEP at the end of the ARMs prolonged the effects of the open lung strategy.